GIANNI VATTIMO „SILPNASIS MĄSTYMAS" IR HERMENEUTIKA. - Mickevičius, Arūnas (Problems / Problemos, 2008)
The article is dedicated to G. Vattimo "weak thought" and its hermeneutical implications. There are three distinguishing features of hermeneutical models -- weak hermeneutics, strong hermeneutics and deep hermeneutics. The article's main problem is to prove thesis that "weak thought" is inseparable from weak hermeneutics. Also article discusses differences between these three hermeneutical models and its implication for understanding of contemporary culture.